OMRON CP1E-NA20DR-A PLC Based Fish Scales and Manure Cleaner Prototype - Teguh Priyono; Wahyu Sapto Aji (Universitas Ahmad Dahlan, 2023)
In fish removal, most of them still use manual cleaning tools whose main crust is human labor so that it can take a not fast time, especially if it is large-scale in cleaning fish and in terms of safety, it is very risky for injured hands due to manual cleaning tools. Aka it is necessary to have a fish cleaning device and clean the dirt automatically, Design and build a prototype of a fish scales and dirt cleaner based on PLC OMRON CP1E-NA20DR-A is a solution in cleaning fish scales and large-scale fish excrement. The way the tool works is that the operator will put the fish into the machine, after the fish is inserted, the sensors at the entrance of the fish will respond to the fish by sending a signal to the PLC so that the PLC will turn on the induction motor as the main crust of the machine, after the engine starts the fish will start to clean the scales and dirt using a knife that has been designed to be used on the machine. Researchers used three fish samples in machine performance experiments to find out how efficient the process of combing and cleaning the dirt was compared to using manual cleaning. The results show that the tool has worked as a whole in scouring and cleaning the dirt as desired by the researcher.